Peers at Work: From the Field to the Lab - Roel van Veldhuizen; Hessel Oosterbeek; Joep Sonnemans (Tinbergen Institute, 2014)
In an influential study, Mas and Moretti (2009) find that worker effort is positively related to the productivity of workers who see him, but not workers who do not see him. They interpret this as evidence that social pressure can reduce free riding. In this paper we report an attempt to reproduce the findings of Mas and Moretti in a lab experiment. Lab experiments have the advantage that they can shut down alternative channels through which workers can influence the productivity of colleagues whom they observe. Although the subjects in our experiment are aware of the productivity of others and although there is sufficient scope for subjects to vary their productivity, we find no evidence of the type of peer effects reported by Mas and Moretti. This suggests that their findings are less generalizable than has been assumed.
Keywords: C91; J24; 330; peer effects; experiment; laboratory experiment